BRYLLUPPET I KRANI: Noter om rites de passage på Balkan - Schwartz, Jonathan (Tidsskriftet Antropologi, 1997)
Jonathan Schwartz: Wedding in Krani: Notes on Balkan Rites of Passage This retrospective essay, inspired by the Biblical wedding in Kana, looks as well towards the future. Its topics are drawn from twenty years of periodic visits to and field work in the Prespa Lake region of Macedonia, bordering on Albania, Greece, and the Republic of Macedonia. Studies of labor migration (pechalba) are orchestrated by weddings, in which villagers are married away to spouses in the metropoles. This is a Virtual rite de passage, especially for the bride. Since the collapse of communism, the breakup of Yugoslavia, and the violence of ethnic cleansing, new imperatives for anthropology have appeared. If once we could direct our interest to the dramatic rites de passage, we now must pay attention to guarding the everyday rights of passage, especially in regions with several ethnic, religious, and linguistic communities. The Prespa Lake village of Krani, half Albanian and half Macedonian, with half its population abroad in diasporas, is an exemplary site for this sort of anthropology.